An aircraft performance model implementation for the estimation of global and regional commercial aviation fuel burn and emissions. (March 2015) - Wasiuk, D.K.; Lowenberg, M.H.; Shallcross, D.E.
Highlights: We develop the Aircraft Performance Model Implementation (APMI) software. We use APMI to update global aviation fuel burn estimates. We use APMI to update global aviation emissions estimates. We compare the results from APMI with the last published set of results for 2006. We discuss the likely reasons for the differences found. Abstract: Estimates of global aviation fuel burn and emissions are currently nearly 10 years out of date. Here, the development of the Aircraft Performance Model Implementation (APMI) software which is used to update global commercial aviation fuel burn and emissions estimates is described. The results from APMI are compared with published estimates obtained using the US Federal Aviation Administration's System for Assessing Aviation's Global Emissions (SAGE) for the year 2006. The number of global departures modelled with the APMI software is 8% lower compared with SAGE and reflects the difference between their commercial air traffic statistics data sources. The mission fuel burn, CO2 and H2 O estimates from APMI are approximately 20% lower than those predicted by SAGE for 2006 while the estimate for the total global aircraft SO x emissions is approximately 40% lower. The estimates for the emissions of CO, HC and NO x are 10%, 140% and 30% higher than those predicted by SAGE respectively. The reasons for these differences are discussed in detail.